Pastoralisme et politiques développementalistes : états de lieux sur les systèmes de tenure foncière pastorale en Afrique Subsaharienne - Habibou Ibrahim; Marc Mormont; Pierre M. Stassart; Boubacar Yamba (VertigO)
This literature review highlights farming policies that affect the Sahelian pastoralism and institutional reforms are underpinned by representations of pastoralism and possibilities that contrast sharply with the knowledge accumulated by the social sciences in recent decades. The central point consists of the pastoral land tenure systems that have been deeply affected by these public policies with population growth and ecological crises, contributing to the destruction of livelihoods of pastoral Community-tees. It also shows that the inventory of knowledge is that sustainable management of rangelands requires consideration of the plurality of actors, their strategies, and their capacity to adapt systems to institutional and environmental contexts changing. This work is a synthesis of research on these land policies and issues (Goxe et al., 2006). This synthesis allows to elucidate bottlenecks mobile pastoral systems to question the representations of pastoralism to the gaze of new realities and challenges of pastoral territories.